Evidence for hepato-biliary transport of immunoglobulin in the antarctic teleost fish Trematomus bernacchii. - ABELLI, Luigi; ZENI, Cristina; COSCIA MR; DE SANTIS A; ORESTE U. (Developmental & Comparative Immunology, 2005)
Purified Trematomus bernacchii bile IgM analysed by SDS-PAGE under reducing and non-reducing conditions consisted essentially of tetramers of the basic structure H2L2. The relative molecular mass of the glycosilated H chain was 76 kDa, while that of L chain was 25 kDa. In addition, the presence in the liver of IgM and m chain-specific mRNA was demonstrated. Immunohistochemistry detected IgH- and IgL-reactivity in perisinusoidal cells, bile canaliculi and pre-ductules. In the anterior intestine, the intraluminal mucus retained a significant Ig-immunoreactivity, while the mucosa housed a limited density of Ig producing cells. These findings strongly indicate that Ig could be transported across the hepatocytes to be secreted into the bile and protect the intestinal epithelium. In addition, extravasated plasma cells accumulated within liver portal tracts and close to the capsule that, in turn, was evenly coated by Ig molecules at the peritoneal surface.